Gender differences in patient and system delay for primary percutaneous coronary intervention: current trends in a Swiss ST-segment elevation myocardial infarction population. Issue 3 (1st April 2019) - Meyer, Matthias R; Bernheim, Alain M; Kurz, David J; O'Sullivan, Crochan J; Tüller, David; Zbinden, Rainer; Rosemann, Thomas; Eberli, Franz R
Abstract: Background: Women with ST-segment elevation myocardial infarction (STEMI) experience greater delays for percutaneous coronary intervention-facilitated reperfusion than men. Whether women and men benefit equally from current strategies to reduce ischaemic time and whether there are gender differences in factors determining delays is unclear. Methods: Patient delay (symptom onset to first medical contact) and system delay (first medical contact to percutaneous coronary intervention-facilitated reperfusion) were compared between women ( n =967) and men ( n =3393) in a Swiss STEMI treatment network. Trends from 2000 to 2016 were analysed, with additional comparisons between three time periods (2000–2005, 2006–2011 and 2012–2016). Factors predicting delays and hospital mortality were determined by multivariate regression modelling. Results: Female gender was independently associated with greater patient delay ( P =0.02 vs. men), accounting for a 12% greater total ischaemic time among women in 2012–2016 (median 215 vs. 192 minutes, P <0.001 vs. men). From 2000–2005 to 2012–2016, median system delay was reduced by 18 and 25 minutes in women and men, respectively ( P <0.0001 for trend, P =n.s. for gender difference). Total occlusion of the culprit artery, stent thrombosis, a Killip class of 3 or greater, and presentation during off-hours predicted delays in men, but not in women. A Killip class of 3 or greater and age, but not gender or delays, were independently associated with hospital mortality. Conclusions: STEMI-related ischaemic time in women remains greater than in men due to persistently greater patient delays. In contrast to men, clinical signs of ongoing chest discomfort do not predict delays in women, suggesting that female STEMI patients are less likely to attribute symptoms to a condition requiring urgent treatment.